Primitive function of the Dunford integral. Issue 1 (July 2021) - Aziz, A; Solikhin,; Sumanto, Y D; Heri, R S U
Abstract: In this paper, Dunford integrals and their primitive functions are discussed. We discuss its properties related to absolutely continuous, strictly absolutely continuous, bounded variation function, strictly bounded variation function and their generalizations. The result is obtained that for each function which integrated Dunford, then the primitive function is a continuous, absolutely continuous, and bounded variation function. Furthermore, its generalized absolutely continuous and generalized bounded variation function.